Gastrointestinal metastases from prostate cancer: a review of the literature. (February 2015) - Maines, Francesca; Caffo, Orazio; Veccia, Antonello; Galligioni, Enzo
ABSTRACT : The availability of active new drugs for the treatment of advanced castration-resistant prostate cancer has significantly prolonged overall survival, thus changing the natural history of the disease and raising the likelihood of observing metastases in atypical sites. This review of the literature describes the frequency, clinical-pathological features and presenting symptoms of non-liver gastrointestinal metastases (GIm) from prostate cancer. Its purpose is to increase clinical awareness of the increasing incidence of such GIm, contributing to the early detection, accurate diagnosis and, when feasible, appropriate management.